Connectivity Optimization through the Development of Feeder Ports for Small Islands in Indonesia - Josua Satria Collins; Meta Diansari (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
This paper aims to discuss the role of the development of feeder ports in small islands in optimizing Indonesia’s connectivity. The research method used is a normative juridical method that is carried out with literature studies and interviews. The result of the study shows that the creation of small island connectivity through the construction of feeder ports will empower these small island communities. When the small island communities are empowered, they will improve their economy, society, and culture, and be able to optimally utilize the marine wealth. In addition, the feeder port development is a form of effective occupation on the small islands and plays an important role in the determination of sovereignty Indonesian archipelago.